Knowledge and Power in the Clinical Setting - McMillan, John (Bioethics, 1997)
In this paper we consider the three categories offered by Howard Brody for understanding power in medicine. In his book, The Healer's Power Brody separates out power in medicine into the categories of Aesculapian, Social, and Charismatic power. We examine these three categories and then apply them to a case. In this case set in an Obstetric ward, a junior member of the medical staff makes a clinical decision about a patient. This clinical decision is overruled by a senior medical staff member who then carries out his plan with disastrous consequences for the woman and her baby. This case challenges the three categories of power offered by Brody and highlights the need for a further category of Hierarchical power to be added to Brody's framework. We conclude by suggesting that there is a need to recognise the discrepancy in power not only between physician and patient but also between senior and junior staff in a clinical setting.